A Case Report of a Double Catastrophe: True Left Ventricular Aneurysm and Ventricular Septal Rupture Complicating Acute Myocardial Infarction and Presenting as Chronic Heart Failure - Khanal, Suraj (Cureus, 2020)
A combination of left ventricular aneurysm (LVA) and ventricular septal rupture (VSR) in an acute myocardial infarction (AMI) patient presenting as heart failure is extremely rare. Here, we report a rare case of concurrent true inferoposterior LVA and VSR secondary to inferior wall myocardial infarction (IWMI) presenting as chronic heart failure (CHF). To the best of our knowledge, this is the third reported case in the literature. A 61-year-old man, who had an IWMI about one month prior, presented with CHF. Echocardiography revealed true inferoposterior LVA and VSR. Coronary angiography revealed double vessel disease involving the right coronary artery (RCA) and left circumflex artery (LCX). Left ventricular angiography confirmed a large posterobasal aneurysm and VSR. The patient underwent successful coronary artery bypass grafting (CABG) and ventriculoplasty along with VSR patch repair.